A single cell culture system using lectin‐conjugated magnetite nanoparticles and magnetic force to screen mutant cyanobacteria. Issue 1 (3rd September 2015) - Arai, Sayuri; Okochi, Mina; Shimizu, Kazunori; Hanai, Taizo; Honda, Hiroyuki
ABSTRACT: Cyanobacteria can be utilized as a potential biocatalyst for the production of biofuels and biochemicals directly from CO2 . Useful mutants of cyanobacteria, which can grow rapidly or are resistant to specific metabolic products, are essential to improve the productivity of biofuels. In this study, we developed a single cell culture system to effectively screen mutant cyanobacteria using magnetite nanoparticles and magnetic force. Lens culinaris Agglutinin (LCA) was selected as a lectin, which binds to the surface of Synechococcus elongatus PCC7942 cells and the LCA‐conjugated magnetite cationic liposomes (MCLs) were developed for magnetic labeling of PCC7942 cells. The MCL‐labeled PCC7942 cells were magnetically patterned at a single cell level by using 6, 400 iron pillars of the pin‐holder device. The device enabled 1, 600 single cells to be arrayed in one square centimeter. We cultured the patterned cells in liquid medium and achieved higher colony‐forming ratio (78.4%) than that obtained using conventional solid culture method (4.8%). Single cells with different properties could be distinguished in the single cell culture system depending on their growth. Furthermore, we could selectively pick up the target cells and subsequently perform efficient isolation culture. The ratio of successful isolation culture using the developed method was 13 times higher than that of the conventional methods. Thus, the developed system would serve as a powerful tool for screening mutant cyanobacteria. Biotechnol. Bioeng. 2016;113: 112–119. © 2015 Wiley Periodicals, Inc. Abstract : Arai and co‐workers report a single cell culture system to effectively select mutant cyanobacteria using magnetite nanoparticles and magnetic force. The magnetically labeled cells were patterned at a single cell level by using iron pillars of the magnetic pin‐holder device in liquid medium. The success ratio of cloned culture of the developed method was noticeably higher than that of the conventional solid culture.